Factors That Influence the Decision to Carry Out Lay Off (Study Case at the Pamong Police Unit Office Praja Kutai Kartanegara - Rifda Khaerani, Thalita; Ramadani , Nurpadillah; Nabil Sabhy, Ahmad Dimas; Yurizky Zuniar , Muhammad Alif; Aulia Fitriani, Dinda (Jurnal Sosial Teknologi, 2024)
Decision-making in carrying out duties is important for police officers. This study was conducted to analyze the factors that affect the decision-making process to carry out duties at the Prajakan Kutai Kertanegara Police Station. This research aims to analyze the factors influencing decisions to implement layoffs at the Office of the Kutai Kartanegara Public Order Police Unit. The research method used is a case study, collecting data through interviews and documentation analysis. The findings highlight several key factors influencing layoff decisions, including economic conditions, organizational policy changes, and internal employee dynamics. These findings provide a better understanding of the factors that need to be considered in human resource management within public service environments such as the Office of the Kutai Kartanegara Public Order Police Unit. The results of this research are expected to provide new insights for the police in increasing effectiveness and efficiency in decision-making to carry out tasks in the field. This is important to maintain public trust in police performance. This case study can be a valuable input for policy makers in the police environment to strengthen a more targeted and responsive decision-making process to the needs of the community.